2022
DOI: 10.1017/s1537592721004114
|View full text |Cite
|
Sign up to set email alerts
|

The Partisans and the Persuadables: Public Views of Black Lives Matter and the 2020 Protests

Abstract: In the spring and summer of 2020, a remarkable number of Americans participated in a remarkable number of protests in support of Black Lives Matter. How did the general public understand these protests, and where does support for the movement stand overall? We answer this question by drawing on several national surveys from 2020 and then examining the results of a framing experiment we conducted in June 2020. We structure the story we find in two parts—the partisans and the persuadables—both of whom are import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…A more recent study about the partisan impact on the attitudes toward BLM also echoes the previous findings. Using the 2020 BLM movement as a case, for instance, Drakulich and Denver (2022) showed that the partisan impact still holds. These studies as well as literature about frontlash collectively suggest that it is important to consider the effect of partisanship on the BLM opinion.…”
Section: Political Ideology and Protest Perceptionmentioning
confidence: 99%
“…A more recent study about the partisan impact on the attitudes toward BLM also echoes the previous findings. Using the 2020 BLM movement as a case, for instance, Drakulich and Denver (2022) showed that the partisan impact still holds. These studies as well as literature about frontlash collectively suggest that it is important to consider the effect of partisanship on the BLM opinion.…”
Section: Political Ideology and Protest Perceptionmentioning
confidence: 99%
“…Political attention to the issue of the police in general has been sharply partisan in the Black Lives Matter Era (e.g. Drakulich et al 2017Drakulich et al , 2020Drakulich and Denver 2022;Taylor 2016). People tend to adopt policy views consistent with their political identification (Lenz 2012).…”
Section: Questions About Views Of Police Use Of Forcementioning
confidence: 99%
“…Although neither hashtag is formally associated with any political party, they have over time become entangled in the increasingly polarized landscape of American political identity [36], [37], and are associated with broader social movements known as Black Lives Matter (BLM) and All Lives Matter (ALM). A recent study showed that Democrats show increased support for the Black Lives Matter movement compared with Republicans [38], though it did not look specifically at hashtags. Less evidence exists about partisanship and All Lives Matter, though a recent qualitative analysis argued that the movement has been far more often invoked by Republican political candidates than by Democrats [39].…”
Section: Introductionmentioning
confidence: 99%